Improving Gold Recovery from Artificial Preg-Robbing Ore by Pre-treatment using Blinding Agent and Resin-in-Leach - Mohammad Zaki Mubarok; Prasetyo Sandha Irianto (Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
In the present paper, the effectiveness of the use of blinding agents, ionic exchanger resins and the combination of them in improving gold extraction from simulated preg-robbing ore is discussed. The blinding agents used were kerosene, diesel oil and pine oil, while the ion exchange resins used were Lewatit Monoplus MP 800, Lewatit AF 5 and guanidine. Preg-robbing conditions were simulated by blending fine activated carbon with ore sample. The investigation results show that the presence of artificial carbonaceous materials at 2% (w/w) in the gold ore significantly reduces gold recovery. Pretreatment of artificial preg-robbing ore prior to cyanidation by mixing with kerosene, diesel oil and pine oil for 0.5h improved gold recovery up to 25.4%. A combination of pre-treatment using blinding agent and a resin in leach (RIL) test using Lewatit MP 800 resin demonstrated a synergistic effect that improves gold recovery up to a level of 99.5%,which is significantly higher than using activated carbon and without pretreatment.